SUICIDAL TENDENCY AS A MANIFESTATION OF SELF-DESTRUCTIVE BEHAVIOR IN WORKERS OF COMMERCIAL SEX - Pototska, Iryna; Grishina, Olga (PSYCHOLOGICAL JOURNAL, 2018)
The purpose of the work is to study suicidal tendency in workers of commercial sex, to determine the target of further psycho-correctional work with this contingent. Contingent and research methods. The study was conducted at the Community Center for Workers of Commercial Sex on the basis of the All Ukrainian Charity Fund “Drop In Center”, which, withan informed consent, surveyed 85 women-workers of commercial sex, residents of the city of Kiev. To establish suicidal tendency, it was used a well-trusted instrument, Columbia Suicide Severity Rating Scale (C-SSRS) which detects and standardizes suicidal thoughts and behavior. Results of the study. The obtained results of the empirical research showed that almost all the surveyed workers of commercial sexhave thoughts about committing suicide, the desire to fall asleep and not to wake up and to cease to exist. Also, almost all of the sample is characterized by general non-specific thoughts about the desire to commit suicide. The main causes of such suicidal ideas are the desire to attract attention, revenge or get a feedback from other people, and the desire to stop their psychological pain. In the study of suicidal actions among workers of commercial sex, it was found that two thirds of workers of commercial sex had stopped attempts to commit suicide in their own experience. Consequently, the results indicated the presence of anti-vital tendencies in women who work as prostitutes, which are an important emotional experience in their lives. The bases can be very different, from refusal to resist the inevitable difficulties, to attract attention, to revenge, to the desire to end the infinite painful mental experiences, but it should be noted that the risk factors of suicide in each case are capable of cumulative and synergistic interaction. Also, the results indicate a high risk of committing suicide among women in this cohort. Conclusion. This study reveals prospects in preventing suicidal tendency and self-destructive behavior in workers of commercial sex. Key words: workers of commercial sex, suicidal tendency, self-destructive behavior.